ANALISIS SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PENGAJUAN KREDIT DENGAN MENGGUNAKAN METODE AHP PADA BTPN KCP UMK PETALING - Rico Rico (Jurnal Ilmiah Media Sisfo, 2014)
With the growth of some small and medium enterprises in the region resulted in the growth of the regional economy will be better. Small and medium enterprises in order to survive and thrive will require additional capital to be gained from banking institutions and non-banking institutions. In banking, lending process is not as easy as turning the palm of the hand. Where the process must pass through several stages and involves several parties to obtain credit decision requiring a relatively long time. Like a few days time it takes to process and file incoming menentukkan can proceed to the survey stage, then a few days time it takes to determine whether it is feasible or not the loan was given to the applicant based on the decision of the BWMK (limit discretionary authority credit). With the length of time it takes to process and determine the credit worthiness of prospective borrowers filing the researchers interested in conducting research on the Bank to help design decision support system (DSS) in the determination of eligibility submission using AHP method. The results of this study are decission support system feasibility of the business loan application expected to assist in providing efficient and appropriate decisions to the Bank's leadership in particular. Keywords: DSS, Credit, AHP Method